The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5585/iji.v7i3.347
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Key Factors Influencing the Use of Online Social Networks in Public Sector Context in the UAE

Abstract: During the past decade, usage of online social network sites has grown dramatically rivaling search engines as the most visited Internet site. The intensive literature review reveals the existing of several studies that have been done on the field of Online Social Network (OSN), but there is a lack of research that deals with usage in the context of public sector organizations. This study aims to employ structural equation modeling via AMOS to analyze 401 valid questionnaires for assessing a model which is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Conversely, the study runs counter to the findings of (Al-Dajjani and et al , 2017), who highlighted that strategic leadership has no discernible positive impact on the quality of services provided by Egyptian universities. The current analysis is in line with previous research Ameen, et al ,2018;Amin, et al ,2019;Amin, et al ,2012 ;Amin, et al ,2011) that demonstrated a substantial relationship between performance impact and service quality. This effect has been explained by the theory that when a public sector employee can take advantage of smart government applications at the location or time where they work, they will search for platforms that are appropriate for their tasks and can also interact with others through them.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, the study runs counter to the findings of (Al-Dajjani and et al , 2017), who highlighted that strategic leadership has no discernible positive impact on the quality of services provided by Egyptian universities. The current analysis is in line with previous research Ameen, et al ,2018;Amin, et al ,2019;Amin, et al ,2012 ;Amin, et al ,2011) that demonstrated a substantial relationship between performance impact and service quality. This effect has been explained by the theory that when a public sector employee can take advantage of smart government applications at the location or time where they work, they will search for platforms that are appropriate for their tasks and can also interact with others through them.…”
Section: Discussionsupporting
confidence: 91%
“…An organization following the two-way symmetrical model of communication and public relations strongly prioritizes its workers and audiences to gather their opinion and, thus, work accordingly. In a similar context, this study applies and follows the relevant model, assuming that media organizations in the United Arab Emirates are giving potential importance to communicate with their audiences (Amin et al, 2019). This communication helps them to create and disseminate desirable content that will be accepted by their audiences (feedback).…”
Section: Two-way Symmetrical Model Of Communication and Public Relationsmentioning
confidence: 99%
“…Table 2 lists empirical research on the acceptance of informatization, focusing on public officers. Although there is already a tremendous amount of research into technology acceptance, we examined the recent research as much as possible, focusing on the time period after the mid-2010s in order to reflect the latest research trends [30][31][32][33][34][35][36][37][38]. As shown in Table 2, the most recent acceptance of informatization studies was conducted in developing countries, because developing countries have applied e-Government in the public sector, and even some developing countries still have difficulty adopting e-Government due to technical and organizational factors.…”
Section: Theoretical Background For the Research Modelmentioning
confidence: 99%
“…As shown in Table 2, the most recent acceptance of informatization studies was conducted in developing countries, because developing countries have applied e-Government in the public sector, and even some developing countries still have difficulty adopting e-Government due to technical and organizational factors. From the aspects of research frameworks, most studies have used a similar framework based on the existing user acceptance model involving the Unified Theory of Acceptance and Use of Technology (UTAUT) [32][33][34][35][36]38]. This study is closest to the user acceptance approach, because GaaP is currently not embedded in the public sector.…”
Section: Theoretical Background For the Research Modelmentioning
confidence: 99%